Osteologia, afinidades filogenéticas e implicações bioestratigráficas de um dinossauro sauropodomorfo do Triássico superior do sul do Brasil - Bem, Fabiula Prestes de (2024)
The origin of dinosaurs has become a hot-topic in recent years, mainly in response to new discoveries, radiometric dating’s, and alternative phylogenetic proposals. Much of this revolution regarding the origin of dinosaurs is related to the discoveries from the Triassic beds of Southern Brazil. Therefore, each new find is received with enthusiasm and could provide new information regarding the initial evolution of dinosaurs. Among the main groups of Dinosauria, Sauropodomorpha is one of the best sampled in the Triassic of Brazil, allowing the construction of macroevolutionary scenarios. In addition, the increasing sample of sauropodomorphs allowed their use as tools in biostratigraphic proposals. In the present dissertation, a new specimen from the municipality of Agudo-RS is described, its phylogenetic affinities are investigated, and a biostratigraphic scenario is constructed according to the new material. CAPPA/UFSM 0327 preserves part of the posterior autopodium e was excavated from the ‘Boi da Guampa Torta’ site, Caturrita Formation. The specimen shares a unique suite of traits with the unaysaurid saurpodomorph Macrocollum itaquii. Furthermore, a phylogenetic analysis suggests affinities between the new material and the species. According to the osteology and phylogenetic affinities, CAPPA/UFSM 0327 is assigned to M. itaquii, representing the first record outside the type-locality. A biostratigraphic scenario is erected for the municipality of Agudo according to the derived phylogenetic affinities of unaysaurids regarding the sauropodomorphs from other localities of this municipality.